Performance analyses in alpine ski racing regarding the characters of slopes and course settings - Waibel, K.; Huber, A.; Spitzenpfeil, P. (Science and Skiing IV, 2008)
INTRODUCTION: Potential Key factors of race courses are frequently discussed by coaches analyzing races and entire seasons. The purpose of the presented study was to detect certain course characteristics that are more likely to decide races than others, and to analyze the individual performance of German Athletes regarding different characteristics. For that reason the race performance of top 30 athletes and the German participants in all GS, SL, and SG World Cup races from Season 2005/2006 to 2006/2007 were monitored. In order to limit the amount of variables, only the declination of the slope and the course setting were considered. An evaluation table for each race course, with four categories for the slope and seven for the course setting, was designed.